Double deletion of tetraspanins CD9 and CD81 in mice leads to a syndrome resembling accelerated aging - Yingji Jin (Nature Portfolio, 2018)
Abstract Chronic obstructive pulmonary disease (COPD) has been recently characterized as a disease of accelerated lung aging, but the mechanism remains unclear. Tetraspanins have emerged as key players in malignancy and inflammatory diseases. Here, we found that CD9/CD81 double knockout (DKO) mice with a COPD-like phenotype progressively developed a syndrome resembling human aging, including cataracts, hair loss, and atrophy of various organs, including thymus, muscle, and testis, resulting in shorter survival than wild-type (WT) mice. Consistent with this, DNA microarray analysis of DKO mouse lungs revealed differential expression of genes involved in cell death, inflammation, and the sirtuin-1 (SIRT1) pathway. Accordingly, expression of SIRT1 was reduced in DKO mouse lungs. Importantly, siRNA knockdown of CD9 and CD81 in lung epithelial cells additively decreased SIRT1 and Foxo3a expression, but reciprocally upregulated the expression of p21 and p53, leading to reduced cell proliferation and elevated apoptosis. Furthermore, deletion of these tetraspanins increased the expression of pro-inflammatory genes and IL-8. Hence, CD9 and CD81 might coordinately prevent senescence and inflammation, partly by maintaining SIRT1 expression. Altogether, CD9/CD81 DKO mice represent a novel model for both COPD and accelerated senescence.